2022
DOI: 10.3390/en15051701
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Assessment of Railway CCTV System Operating Reliability

Abstract: The article reviews the history and the direction of development for railway CCTV (Closed-Circuit TeleVision) systems. The authors described the CCTV system at PKP Polskie Linie Kolejowe S.A. and the associated network and server infrastructure. The authors proposed an operational model for a centralized CCTV system that assumes states of partial fitness, in accordance with the regulations of the national railway infrastructure administrator. The aim of the paper is to review, analyse, and evaluate the operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…When supplying ICT systems, especially in critical infrastructure facilities [66][67][68], it may not be enough [69]. Therefore, the power supply from three independent sources is then used (e.g., primary power supply and two standby power supplies, as power supply from a separate power line and the use of a power generating unit) [70][71][72][73]. A structural sketch of such a power supply solution for an ICT system containing three independent energy sources is shown in Figure 1.…”
Section: State-of-the-artmentioning
confidence: 99%
“…When supplying ICT systems, especially in critical infrastructure facilities [66][67][68], it may not be enough [69]. Therefore, the power supply from three independent sources is then used (e.g., primary power supply and two standby power supplies, as power supply from a separate power line and the use of a power generating unit) [70][71][72][73]. A structural sketch of such a power supply solution for an ICT system containing three independent energy sources is shown in Figure 1.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Indeed, important deliberations on the traffic situation can be also found in the field of air transport [35][36][37]. The experience of the authors and the negative impacts of checks on device availability identified in the course of test program execution, as described in [38][39][40] is, therefore, a motive for commencing work on developing a method supporting test set determination.…”
mentioning
confidence: 99%